Periodic crack-model of comb transducers: efficiency and optimization - DANICKI, E. (Archives of Acoustics, 2000)
A model for a comb transducer is investigated in which the comb-sample interface is modeled by a periodic system of cracks. Leaky interface crack waves are generated by a normal incident shear bulk wave beam or by an equivalent excitation of the comb teeth at the interface. The generation efficiency is analyzed in systems where both the comb and the sample halfspaces are from the same material, steel or aluminium, for different teeth width and period, and for the case of solid contact between the two halfspaces between cracks; the other case of sliding contact is discussed briefly. Numerical results show that up to 25% of the incident power can be transformed into interface crack waves by a comb tooth. Optimal number of comb teeth is estimated, and the transducer frequency response is discussed. Approximated relationships are presented that may help designing a comb.